2016
DOI: 10.21273/jashs.141.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Hybridization between Eggplant and Wild Relatives from Different Genepools

Abstract: Wild relatives represent a source of variation for many traits of interest for eggplant (Solanum melongena) breeding, as well as for broadening the genetic base of this crop. However, interspecific hybridization with wild relatives has been barely used in eggplant breeding programs. As initiation of an introgression breeding program we performed 1424 interspecific hybridizations between six accessions of eggplant from the Occidental and Oriental groups and 19 accessions of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 41 publications
(73 reference statements)
8
98
1
Order By: Relevance
“…The popular variety is based on local preferences [37]. The secondary genepool species are the reserve of useful genes for the improvement of present-day varieties, but because of breeding barriers, they are not exploited to their full potential [4,42,43]. Therefore, most of the time, the local germplasm is used extensively which might have resulted in the lower genomic diversity of eggplant, which has further resulted in the yield stagnation and susceptibility to diseases [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popular variety is based on local preferences [37]. The secondary genepool species are the reserve of useful genes for the improvement of present-day varieties, but because of breeding barriers, they are not exploited to their full potential [4,42,43]. Therefore, most of the time, the local germplasm is used extensively which might have resulted in the lower genomic diversity of eggplant, which has further resulted in the yield stagnation and susceptibility to diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…Eggplant (Solanum melongena L.; Solanaceae) is a highly diverse vegetable with a large array of phenotypically variable local varieties. Several studies show that eggplant can be hybridized with many wild related species, opening the way for introgression breeding by using wild relatives as donors of variation [3,4]. Although the center of origin of eggplant is the Indo-Chinese region [5], the greatest diversity in its wild relatives is found in Africa [6].…”
Section: Introductionmentioning
confidence: 99%
“…Defining genepools in large genera such as Solanum is challenging and we have approached this with a compromise solution that takes into account phylogenetic relationships and crossability (Vorontsova et al, 2013; Plazas et al, 2016). The concept presented here uses primarily phylogenetic relationships to define GP2, and GP3 includes less closely related but useful species which have previously been used in eggplant breeding but that thus far cannot be easily crossed with S. melongena (Plazas et al, 2016). Our newly suggested genepool concept for eggplant includes one wild species (the wild progenitor of the eggplant, S. insanum ) in GP1, 48 species in GP2, and three more widespread weedy species with native distributions in the New World in GP3 (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…They separated S. insanum into three major genetic groups and suggested that geographic isolation and limited gene flow have structured the genetics of this species in the study area. This high genetic divergence among populations suggests that further population level sampling across the range of S. insanum will uncover genetic novelty worth conserving in genebanks, especially given the lack of reproductive barriers between S. insanum and S. melongena (Davidar et al, 2015; Plazas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation